Characteristics 0f Tinnitus and its Association with Clinico-demograhic Factors & Mental Health. - Maria Murtaza; Ghulam Saqulain; Rafaqat Ali Rao (Journal Riphah College of Rehabilitation Sciences, 2024)
Objectives: To determine the characteristics of tinnitus and its association with clinical and demographic variables including psychological health.